SYSTEM-SYNERGETIC APPROACH IN RESEARCH OF THE FUNCTIONING OF THE BANK SYSTEM - Ткачук, Наталія (Socio-economic relations in the digital society, 2019)
The article considers the essence of the banking system according to the systemic and synergistic approaches. The banking system was formed and develops as a result of the cooperative interaction of all its elements, and its functioning is accompanied by constant infl uences by both internal and external factors. The system characteristics of the banking system: integrity, hierarchy, integrativity, communication and others are solved. Th e need for a synergistic approach in the study of the features of the banking system in a synergistic market is proved. It was proposed to supplement the list of system characteristics of the banking system with such features as: complexity, dynamism, openness, non-linearity, disequilibrium, coherence and ability to selforganization, which makes it possible to understand its essence more complete and realistic. The economic content of these concepts as features of the banking system by the synergetic approach is highlighted. In particular, the banking system is an economic system, refers to the type of open, complex objects that can be described by integration, thermodynamic parameters, fully reflect the exchange of material and financial resources with the environment. It also diff ers by dynamism and non-equilibrium of its development. The openness of the banking system is considered as a wide range of vertical and horizontal informational, economic and other relations with the external environment. The dynamism of the banking system is determined by the fact that its structure, goals and relations between the elements are non-permanent, they change and evolve over time. The processes of self-organization can occur only in those systems that have a high level of complexity and a large number of elements, the links between which are not strictly determined, but have a probabilistic nature.